Farmer’s right in Malaysia: revisiting the implementation of Protection of New Plant Varieties Act (PNPVA) 2004 - Ismail, Suzi Fadhilah (2021)
This is the slides for the presentation made in the UiTM International Conference on Law & Society 2021 (UiTM i-CLaS 2021) held online on 1 - 2 November 2021.